How do schools in Indonesia fight against cyberbullying? - Wulandari, Aprilianti; AW, Suranto (Universitas Negeri Yogyakarta, 2023)
The development of highly advanced technology has changed the pattern of people's lives in fulfilling information needs. All forms of information obtained will spread very quickly and even difficult to control. We cannot avoid that currently people from all walks of life are increasingly